2019
DOI: 10.1103/physrevd.100.065013
|View full text |Cite
|
Sign up to set email alerts
|

Entanglement extracted from vacuum into accelerated Unruh-DeWitt detectors and energy conservation

Abstract: We consider a pair of two-level Unruh-DeWitt detectors accelerated uniformly in the Minkowski vacuum of a massless neutral scalar field, and analyze, within the perturbation theory, the entanglement extracted from the vacuum into the Unruh-DeWitt detectors when the switching of the detectors are performed adiabatically enough at the asymptotic past and future. We consider the cases where the detectors are accelerated parallelly, anti-parallelly, and in differently orientated directions. We show that entangleme… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 30 publications
1
30
0
Order By: Relevance
“…Having said our motivation in the introduction, let us now talk about the model which will be dealt with in this article. The model on which we will concentrate here was originally introduced in [38][39][40]. Therefore, without going into the details of this and the derivation of the required formulas, the final expressions which are needed in this paper will be summarised here.…”
Section: Model Set-up: a Summary Of The Main Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Having said our motivation in the introduction, let us now talk about the model which will be dealt with in this article. The model on which we will concentrate here was originally introduced in [38][39][40]. Therefore, without going into the details of this and the derivation of the required formulas, the final expressions which are needed in this paper will be summarised here.…”
Section: Model Set-up: a Summary Of The Main Resultsmentioning
confidence: 99%
“…It should be noted that in initial works [4,9] the authors found these eigenvalues to be dependent on quantities estimated from positive frequency Wightman functions connecting different spacetime events of the same or different detectors. However, recent rigorous investigations [38][39][40] have suggested proper time ordering into the picture, which results in the inception of Feynman propagator rather than Wightman function in the estimation of the eigenvalues. These recent methods provide a meticulous and more general formulation for the understanding of entanglement harvesting.…”
Section: Jhep07(2021)124mentioning
confidence: 99%
See 3 more Smart Citations